The Effect of A Strategy Bayer on Subject Achievement of Biology And Trilateral Intelligence Among Fourth Year Science Students (Journal of the College of Basic Education, 2025)
the research aims to identify (The effect of a strategy Bayer on subject achievement of biology and trilateral intelligence among fourth year science students) . To verify the aim of the research, we formulated the following two null hypotheses:there is no statistically significant difference at the significance level (0,05) between the average grades of the experimental group students who studied according to the strategy Bayer , and the average grades of the control group students who studies according to the usual method in achievement the biology subject . there is no statistically significant difference at the significance level (0,05) between the average grades of the experimental group students who studied according to the strategy Bayer , and the average grades of the control group students who studies according to the usual method in the triple intelligence .In order to verify the two hypotheses, the research population was limited to fourth to fourth year science students in secondary and middle school in the Baghdad Education Directorate / Al- Rusafa First / North Baghdad Department section, Al- Husseiniyah District, their number is large (940 ) students, the Boy science secondary school was intentionally chosen to be the research sample this is due to the cooperation of the school administration with the researcher, sections (A) and (B) were randomly selected with (40) students for the experimental group studies biology a according to Bayer’s strategy and (40) students in the control group who study the same subject a according to the usual method . the two research groups were rewarded with variables ( previous achievement, previous information in biology, triple intelligence) the scientific subject was determined in the second , third , fourth , and fifth chapters of the biology course, 12 edition, the year 2022 Teaching plant were prepared for the two research groups, Behavioral objectives were formulated for the subjects chapters, which numbered (210) behavioral objectives, the researcher built the achievement test for the biology subject, and adopted the triple intelligence test, their psychometric properties were confirmed, it is the internal and external integrity of experience, the following results were reached: 1- the experimental group outperformed the control group with astatically significant difference in achieving biology . 2- the experimental group outperformed the control group with astatically significant difference in the triple intelligence . In light of the research results, the researcher presented an number of recommendations and proposals